취약계층 골관절염 여성의 건강증진 프로그램 효과 - 이명숙(Myung Suk Lee); 임현자(Hyun Ja Lim); 김정숙(Jung Suk Kim) (지역사회간호학회지, 2011)
Purpose: This study was to develop and evaluate a health promotion program for women with osteoarthritis. Methods: The research adopted the nonequivalent control group pretest-posttest design. The subjects were 34 in the experimental group and 34 in the control group sampled among vulnerable women aged over 40. The independent variable was the health promotion program, and the dependent variables were perceived health status, balance, K-WOMAC, depression, life satisfaction and health promoting behavior. The health promotion program was performed for 50minutes each session, twice a week and for 8 weeks. Data were collected from July 1 to September 11, 2010. Results: The experimental group showed significant differences in perceived health status, balance, WOMAC pain, WOMAC difficulty of performing activity, depression, and health promoting behavior compared to the control group. There was no significant difference in WOMAC stiffness, waist, weight, and life-satisfaction. Conclusion: The results of this study suggest that the health promotion program can be applied in degenerative arthritis education to improve self-care.